Preliminary Design of Algae Cultivation Bioreactor - Sulaiman, Syahidzil Mokhaizil; Abdul Ghafir, Mohammad Fahmi; Manshoor, Bukhari; Sunar, Norshuhaila Mohamed (Journal of Emerging Technologies and Industrial Applications, 2023)
The aim of this project is to comprehensively study the background design of an algae cultivation bioreactor, identify its working principle, and develop engineering drawings while conducting a design analysis of an existing algae bioreactor cultivation in RECESS, UTHM. The objective is to enhance the efficiency and productivity of the bioreactor system for sustainable algae cultivation. SolidWorks is a solid modelling computer-aided design (CAD) and computer-aided engineering (CAE) computer program that will be used to create detailed and accurate 3D models of an algae cultivation bioreactor. The 3D designs for the components will be construct before the analysis using Ansys. Two analyses will be conducted using it which is the thermal analysis on the solar panel and the hydrostatic pressure analysis on the water tank. The result is will show either that the water tank was constructed and safe to use. Both of the analyses will be conducted using Ansys Workbench and helped to understand the behaviour of the water tank and the solar panel.